2016
DOI: 10.3389/fnins.2016.00583
|View full text |Cite
|
Sign up to set email alerts
|

Population Coding of Facial Information in the Monkey Superior Colliculus and Pulvinar

Abstract: The superior colliculus (SC) and pulvinar are thought to function as a subcortical visual pathway that bypasses the striate cortex and detects fundamental facial information. We previously investigated neuronal responses in the SC and pulvinar of monkeys during a delayed nonmatching-to-sample task, in which the monkeys were required to discriminate among 35 facial photos of five models and other categories of visual stimuli, and reported that population coding by multiple SC and pulvinar neurons well discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…These data are consistent with anatomical connectivity studies in macaques that demonstrated projections from the medial ventral pulvinar to the lower lip of the STS (Grimaldi et al, 2016) and projections from ventral temporal cortex (around area TF) to lateral portions of the pulvinar (Benevento and Rezak, 1976) as well as an electrical stimulation study showing evoked activity within the ventral medial pulvinar from stimulation of face patches in the lower bank of the STS (Moeller et al, 2008). Previous studies have demonstrated responsiveness in the primate pulvinar to object features at the neuronal level (Nguyen et al, 2013;Nguyen et al, 2016). To our knowledge, this is the first demonstration of image category-selective visual responses within the human thalamus.…”
Section: Discussionsupporting
confidence: 90%
“…These data are consistent with anatomical connectivity studies in macaques that demonstrated projections from the medial ventral pulvinar to the lower lip of the STS (Grimaldi et al, 2016) and projections from ventral temporal cortex (around area TF) to lateral portions of the pulvinar (Benevento and Rezak, 1976) as well as an electrical stimulation study showing evoked activity within the ventral medial pulvinar from stimulation of face patches in the lower bank of the STS (Moeller et al, 2008). Previous studies have demonstrated responsiveness in the primate pulvinar to object features at the neuronal level (Nguyen et al, 2013;Nguyen et al, 2016). To our knowledge, this is the first demonstration of image category-selective visual responses within the human thalamus.…”
Section: Discussionsupporting
confidence: 90%
“…To analyze representation of the stimulus by population activity of the SC neurons, activity of the SC neurons with central RFs (n = 32) was analyzed by MDS (Le et al, 2013(Le et al, , 2014Nguyen et al, 2013Nguyen et al, , 2014Nguyen et al, , 2016Dinh et al, 2018). MDS constructs a stimulus space in which relationships among stimuli are shown (Young, 1987).…”
Section: Multidimensional Scaling (Mds) Analysismentioning
confidence: 99%
“…) . Fast emotional face processing with responses in the amygdala at 74 ms has been demonstrated in epilepsy patients being evaluated for temporal lobectomy; in nonhuman primates, pulvinar recordings show 50‐ms latency responses to face‐like stimuli, including cartoon faces . The traditional conception of the function of the amygdala as a “fear hub” (responsive to visual images of fear alone) has been challenged by recent fMRI studies, which have shown that the amygdala was comparably active in response to facial emotional expressions indicating anger, disgust, fear, happiness, and sadness …”
Section: The Psychiatry Of Cervical Dystonia and Disordered Social Comentioning
confidence: 99%